The science of God : the convergence of scientific and biblical wisdom - Schroeder, Gerald L (New York : Broadway Books, 1998)
Explains surprising paralles between biblical teaching and findings in biochemists, paleontologist, astrophysicists and physicists
Has sciene replaced the Bible? The great debate -- The new convergence: science, scientists, and the Bible -- The age of our universe: six days and fifteen billion years -- The six days of Genesis -- The nature of God: biblical expectations for an infinite yet immanent creator -- Life: its origins and its evolution -- Evolution: statistics versus random mutations -- The watchmaker and the watch -- The origin of humankind -- The science of free will -- Why bad (and good) things happen -- Bread from earth: a universe tuned for life -- Epilogue: well, what about dinosaurs?
Originally published: New York : Free Press, 1997
Includes bibliographical references (pages 207-216) and indexes
Keywords: Bible and science